Eats for Earth: Understanding Consumer Intentions to Buy Suboptimal Food - Yuliasih Puji Rahayu Hardy; Mas Wahyu Wibowo (ARE Publisher, 2026)
Food waste remains a major global sustainability challenge, particularly at the consumer level where suboptimal food is frequently rejected despite being safe and nutritious. Objectives: This study aims to examine the effects of attitude, subjective norms, perceived behavioral control, and food waste awareness of consequences on consumers purchase intention of suboptimal food. The study integrates the Theory of Planned Behavior (TPB) and the Value-Belief-Norm (VBN) theory to explain pro-environment purchasing behavior. Methodology: A quantitative approach was applied using survey data collected from 228 consumers. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Finding: The results show that attitude and subjective norms have a strong and significant positive effect on purchase intention, while food waste awareness of consequences also contributes significantly. Perceived behavioral control, however does not significantly influence purchase intention. Conclusion: These findings suggest that psychological and moral factors play a critical role encouraging consumers to purchase suboptimal food and reduce food waste. The study provides important implications for marketers, policymakers, and sustainability campaigns aimed at promoting sustainable consumption behavior.